PELATIHAN OPTIMALISASI BIAYA MODAL BAGI PEBISNIS PEMULA - Dasman, Sunita (DPPM Universitas Pelita Bangsa, 2025)
Financial management is a crucial aspect that determines the success and sustainability of a business. One of the key elements in financial management is understanding and managing the cost of capital. The training program